HUBUNGAN ANTARA KETEBALAN LEMAK TRICEPS (KLT) DAN KADAR HIGH SENSITIVITY C-REACTIVE PROTEIN (hs-CRP) PADA MAHASISWA OBES DAN TIDAK OBES DI FAKULTAS KEDOKTERAN UNIVERISITAS SAM RATULANGI MANADO - Gansareng, Deril; Bolang, Alexander S. L.; Mayulu, Nelly (Universitas Sam Ratulangi, 2015)
Abstract: Socio-economic conditions are on the rise in developed countries and some developing countries allow for lifestyle changes. One of these changes is the consumption of low carbohydrate and high fat diet that can lead to unbalanced nutrition changes. Generally obesity causes the accumulation of fat in the subcutaneous and other tissues. The increasing prevalence of obesity is apparently closely related to the increasing prevalence of metabolic syndrome. Increased incidence of metabolic syndrome is in line with the increase in subcutaneous fat. Hs-CRP is a kind of protein synthesized in the liver as a response to stimuli during the acute inflammatory phase. This study aimed to determine the correlation of the thickness of the triceps muscle fat with hs-CRP level among the students of the Faculty of Medicine, University of Sam Ratulangi. This was an observational study with a cross-sectional approach. Data were analyzed statistically by using the Mann Whitney U test which showed significant differences (p = 0.000). The Spearman test showed a correlation coefficient (r) of 0.427 and a p value of 0.001 <Î± = 0.05 level. Conclusion: There was a significant correlation between the thickness of triceps fat and hs-CRP levels in obese and nonobese students in the Faculty of Medicine, University of Sam Ratulangi.Keywords: thick fat triceps, hs-CRP.Abstrak: Kondisi sosial ekonomi yang semakin meningkat di negara maju dan beberapa negara berkembang memungkinkan terjadinya perubahan gaya hidup. Salah satunya ialah perubahan pola makan dengan diet rendah karbohidrat dan tinggi lemak sehingga dapat menyebabkan perubahan gizi yang tidak seimbang. Obesitas umumnya menyebabkan akumulasi lemak pada daerah subkutan dan jaringan lainnya. Peningkatan prevalensi obesitas ini ternyata berkaitan erat dengan meningkatnya prevalensi kejadian sindroma metabolik. Peningkatan kejadian sindroma metabolik sejalan dengan peningkatan lemak subkutan. Hs-CRP merupakan protein yang di sintesis di hati sebagai responden terhadap rangsangan pada saat inflamasi fase akut. Penelitian ini dilakukan untuk mengetahui Ketebalan Lemak Triseps (KLT) dengan kadar hs-CRP pada Mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi Manado. Jenis penelitian yang dipakai ialah observasional analitik dengan pendekatan potong lintang. Hasil analisis statistik dengan menggunakan uji Mann Whitney U menunjukkan terdapat perbedaan bermakna (p=0,000). Hasil uji Spearmen menunjukkan nilai koefisien korelasi (r) sebesar 0,427 dan nilai Ï = 0,001 < Î± = 0,05. Simpulan: Terdapat hubungan bermakna antara ketebalan lemak triseps dan kadar hs-CRP pada mahasiswa obes dan tidak obes di Fakultas Kedokteran Universitas Sam Ratulangi Manado.Kata kunci: Lemak Triseps, hs-CRP.